Theoretical basis of stage evolution differentiated learning ideas of pupils in average general educational institutions in the second half of the xx century. - Наливайко, О. О. (Scientific notes of the pedagogical department, 2017)
The article reflects the process of development of the idea differentiated learning of pupils of average educational institutions in pedagogical science of thesecond half the XX century. Obtained and summarized three stages of evolution of the idea of differentiated learning in the school in study period.